Pyrancoumarin derivative LP4C targeting of pyrimidine de novo synthesis pathway inhibits MRSA biofilm and virulence - Liu, Yongsheng; Su, Shan; Yu, Moxi; Zhai, Dongshen; Hou, Yachen; Zhao, Hui; Ma, Xue; Jia, Min; Xue, Xiaoyan; Li, Mingkai (Frontiers in Pharmacology, 2022)
Staphylococcus aureus poses a serious public health threat because of its multidrug resistance and biofilm formation ability. Hence, developing novel anti-biofilm agents and finding targets are needed to mitigate the proliferation of drug-resistant pathogens. In our previous study, we showed that the pyrancoumarin derivative 2-amino-4-(2,6-dichlorophenyl)-3-cyano-5-oxo-4H, 5H- pyrano [3,2c] chromene (LP4C) can destroy the biofilm of methicillin-resistant S. aureus (MRSA) in vitro and in vivo. Here, we further explored the possible mechanism of LP4C as a potential anti-biofilm drug. We found that LP4C inhibits the expression of enzymes involved in the de novo pyrimidine pathway and attenuates the virulence of MRSA USA300 strain without affecting the agr or luxS quorum sensing system. The molecular docking results indicated that LP4C forms interactions with the key amino acid residues of pyrR protein, which functions as the important regulator of bacterial pyrimidine synthesis. These findings reveal that pyrancoumarin derivative LP4C inhibits MRSA biofilm formation and targeting pyrimidine de novo synthesis pathway.